Recovering facial reflectance and geometry from multi-view images - Song, Guoxian; Zheng, Jianmin; Cai, Jianfei; Cham, Tat-Jen (Image and vision computing, 2020)
While the problem of estimating shapes and diffuse reflectances of human faces from images has been extensively studied, there is relatively less work done on recovering the specular albedo. This paper presents a lightweight solution for inferring photorealistic facial reflectance and geometry. Our system processes video streams from two views of a subject, and outputs two reflectance maps for diffuse and specular albedos, as well as a vector map of surface normals. A model-based optimization approach is used, consisting of the three stages of multi-view face model fitting, facial reflectance inference and facial geometry refinement. Our approach is based on a novel formulation built upon the 3D morphable model (3DMM) for representing 3D textured faces in conjunction with the Blinn-Phong reflection model. It has the advantage of requiring only a simple setup with two video streams, and is able to exploit the interaction between the diffuse and specular reflections across multiple views as well as time frames. As a result, the method is able to reliably recover high-fidelity facial reflectance and geometry, which facilitates various applications such as generating photorealistic facial images under new viewpoints or illumination conditions. •a reliable and lightweight solution for faithfully recovering facial appearances with specularity•multi-view face model fitting, facial reflectance inference and geometry refinement.•optimization algorithms to recover the specular albedo and to refine the normal map for surfaces.